2‐Methoxypropanol‐1 [MAK Value Documentation in German language, 2018]. Issue 2 (24th April 2018) - Hartwig, A.; ,
Abstract: The German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has re‐evaluated the maximum concentration at the workplace (MAK value) for 2‐methoxypropanol‐1 [1589‐47‐5 ]. Available publications and unpublished study reports are described in detail. Critical effects of 2‐methoxypropanol‐1 are its irritancy and teratogenicity. A MAK value of 5 ml/m 3 had been set. By analogy with 2‐methoxypropylacetate‐1, this value is now reaffirmed. Also, by analogy with 2‐methoxypropylacetate‐1 Peak Limitation Category I with excursion factor of 2 is set. 2‐Methoxypropanol‐1 ether remains assigned to Pregnancy Risk Group B and also remains designated with an "H" (for substances that can be absorbed through the skin in toxicologically relevant amounts).